Предмет: Алгебра,
автор: marinaKurkina
Преобразуйте в многочлен: (a-x)²+(a+x)²
2(x+6)²-(20x+70)
Ответы
Автор ответа:
0
1)(a-x)²+(a+x)²=a²-2ax+x²+a²+2ax+x²=2a²+2x²
2)2(x+6)²-(20x+70)=2x²+24x+72-20x-70=2x²+4x+2
2)2(x+6)²-(20x+70)=2x²+24x+72-20x-70=2x²+4x+2
Автор ответа:
0
(а-х)²+(а+х)²=а²-2ах+х²+а²+2ах+х²=2а²+2х².
2(х+6)²-(20х+70)=2(х²+12х+36)-20х-70=2х²+24х+72-20х-70=2х²+4х+2.
Похожие вопросы
Предмет: Алгебра,
автор: djzbd
Предмет: История,
автор: 56fd
Предмет: Литература,
автор: jsjdnssn627
Предмет: Химия,
автор: drakosha725
Предмет: Математика,
автор: putimova82